Normalization of eosinophil count is predictive of oxygen weaning over the course of COVID-19 infection among hospitalized adults during the first wave of 2020 pandemic - Davido, Benjamin; Jaffal, Karim; Saleh-Mghir, Azzam; Vaugier, Isabelle; Bourlet, Stephane; De Truchis, Pierre; Annane, Djillali (Frontiers in Immunology, 2024)
Background: Understanding Covid-19 outcomes remains a challenge. While numerous biomarkers have been proposed for severity at admission, limited exploration exists for markers during the infection course, especially for the requirement of oxygen therapy.This study investigates the potential of eosinophil count normalization as a predictor for oxygen weaning during the initial wave of the pandemic.Methods: Retrospective study, conducted between March-April 2020 (first wave), among adults admitted directly to a medicine ward. Biological abnormalities, including lymphocyte count, eosinophil count, and CRP were gathered daily during the first week of admission according to oxygen level. In case of worsening, oxygen level was censored at 15 L/min. The primary aim was to assess whether eosinophil count normalization predicts a subsequent decrease in oxygen requirements.Results: Overall 132 patients were admitted, with a mean age of 59.0±16.3 years.Seventy-two percent of patients required oxygen, and 20.5% were admitted to the intensive care unit after a median delay of 48 hours. The median CRP at admission was 79 (26-130) mg/L, whereas the eosinophil count was 10 (0-60) /mm 3 . Eosinophil count normalization (≥100/mm 3 ) by day 2 correlated significantly with decreased oxygen needs (<2L) with HR=3.7 [1.1-12.9] (p=0.04). Likewise, CRP<80 mg/L was associated with reduced oxygen requirements (p<0.001). Predictors, including underlying chronic respiratory disease, exhibited a trend toward a negative association (p=0.06).The study highlights the relationship between eosinophil count and CRP, with implications for predicting oxygen weaning during Covid-19. Further research is warranted to explore the relevance of these biomarkers in other respiratory infections.